Quality indicators and commodity of apple varieties - I.A., BEYAHMEDOV (The journal of contemporary issues in business and government, 2021)
The article was informed about research results related to the commodity and quality indicators to Azerbaijan introduced varieties of apples. The analysis carried out in the north-east of the country- in the conditions of Guba, Gusar, Shabran regions on the cultivated apple varieties. This time were analyzed in the following varieties: The sorts as Qala, Conaqored, Qrani Smit, Fuji, Simirenko reneti, Qolden Delişse x 972, Conaqold growned on the grafted of the wild forest apple in the area 5x4 m in 2005 in the village Timiryazev of the Quba region; The sorts as Conaqored, Golden Reinders, Grani Smith, Aydared, Red Vinter, Fuji growned on the grafted of M-9 in the area 4x1,25m in 2008-2009 in the village Teni hayat of the region Gusar; The sorts as Qala, Conaqored, Qrani Smit, Fuji, Simirenko reneti, Qolden Delişse x 972, Conaqold growned on the grafted of M-9 in the area 5x3 in 2008-2009 in the village Dashliyataq of the region The research was carried out on the generally accepted methods on basics of gardening. This time,the average weight of the fruit was on the basis of the average weight of 100 fruit: many large - weighing more than 175 g; large - weighing 175-126 g; average - mass 125-101q; small - weighing 100-76 g; very small - weighing less than 76 grams. The study chemical composition of apple varieties was carried out in the technology, biochemistry and fruit processing laboratory of SRIFT. This time, basically has been identified total and soluble dry substance, sugar, coloring ingredients, ascorbic acid. The soluble dry matter by refractometric method, vitamin C with the help of Tilsman reagent, sugars according to Bertrand, coloring items according to Leventhal and Neybayep has been identified . It was determined that grafted onto the cultivated varieties wild apple woods product intended for processing industry in comparison, in varieties grown on grafted clone more storage and for use in case of fresh fruit. The analysis determined that Cır Hajı from local varieties indicators lag behind a lot introduced new apple varieties despite the fact that dominating according to the chemical composition the apple varieties introduced earlier.